A Standardized Anesthetic and Surgical Clinical Pathway for Esophageal Resection: Impact on Length of Stay and Major Outcomes. Issue 2 (1st March 2015) - Porteous, Grete H.; Neal, Joseph M.; Slee, April; Schmidt, Henner; Low, Donald E.
Abstract : Background and Objectives: Esophageal cancer is a leading cause of cancer death worldwide, and esophageal resection is associated with extremely high perioperative morbidity and mortality. A perioperative clinical pathway for esophagectomy patients in which anesthetic care is both integral and standardized has not been described previously. Methods: A continuously refined clinical pathway for perioperative care of the esophagectomy patient has been developed at the Virginia Mason Medical Center over the past 22 years. Ongoing data collection records patient demographics, comorbidities, tumor stage, and various outcomes including intensive care unit and hospital length of stay, surgical complications, and morbidity and mortality rates. Results: Over time, patients presenting for surgical treatment of esophageal cancer have had significantly higher Charlson comorbidity scores and a higher incidence of diabetes mellitus, hypertension, liver disease, and history of deep vein thrombosis or pulmonary embolism. During the same period, intensive care unit and hospital length of stays have decreased, whereas most complication rates have remained stable despite more advanced tumor stage and increased use of neoadjuvant chemoradiotherapy. In-hospital and 30-day mortality rates are well below national averages at 0.5% each. Conclusions: We present a detailed anesthetic and surgical perioperative pathway for esophageal resection, along with evidence of improved or stable patient outcomes despite an increase in comorbidity burden and increasingly advanced tumor stage.